Solutions to penicillium taxonomy crucial to mycotoxin research and health - Paterson, R. R. M. (2004)
The stability of taxonomy within Penicillium is reviewed with respect to mycotoxin production. Identification remains difficult despite the availability of modern methods. Proficiency testing is rare and conventional identifications do not inform reliably as to whether mycotoxins were detected/produced. A solution which consists of identifying a Penicillium strain as terverticillate and then undertaking mycotoxin analysis is described.